ENEAGRAM SEBAGAI PETA GAMBARAN DIRI - John Tondowidjojo (Lembaga Penelitian STKIP Widya Yuwana, 2018)
The Enneagram is a personality type system of nine interconnected personality archetypes. These nine types are connected to the other four composed around the symbolic diagram. The Enneagram symbol has an ancient and mysterious origin. This symbol is an elegant model of some basic laws of the universe expressed in mathematical terms that reflect patterns seen in nature, including in the human ego or personality. Archetypes are models or prototypes that help us distinguish and understand the universal pattern. According to Carl Jung, the archetype is a